The Strategic Leadership Role of Principals in Formulating Islamic Value-Based School Health Management: A Case Study of SMP Sains Terpadu Darussa'adah Pace - M. Burhanuddin Ubaidillah (Pascasarjana Manajemen Pendidikan Islam STAI Darussalam Nganjuk, Indonesia, 2026)
In response to the growing emphasis on holistic student well-being within educational settings, this study investigates the strategic leadership role of principals in integrating Islamic values into school health management, using SMP Sains Terpadu Darussa'adah Pace, an Integrated Islamic School (Sekolah Islam Terpadu - SIT), as a case study. Recognizing the unique position of SIT schools in harmonizing faith and science, including health, and the principal's crucial function as both strategic leader and guardian of core values, the research aimed to analyze the specific role and strategies employed by the principal in developing and implementing Islamic value-based health management. Utilizing a qualitative case study methodology, the researcher gathered data through in-depth interviews with the principal, teachers, health coordinator, students, and committee members; observations of health activities, facilities, and school culture; and analysis of relevant documents like the school vision/mission, policies, lesson plans, and reports. The findings provide a detailed description of the principal's strategic leadership across functions (vision setting, planning, organizing, leading, monitoring), identify the specific Islamic values integrated into health strategies, outline key health programs championed by the principal, and highlight both enablers and challenges encountered. The study concludes that principals serve as pivotal catalysts for embedding Islamic values into the core of school health management, with SMP Sains Terpadu Darussa'adah Pace exemplifying effective leadership in aligning health strategies with Islamic principles, leading to specific recommendations for principals and Islamic schools aiming for holistic education and health promotion.